Analisis Fungsi Pakaian Karnaval di Yogyakarta Menurut Roland Barthes dan Fungsi Seni Edmund Burke Felmand - Deni Setiawan; Timbul Haryono; M. Agus Burhan (Bina Nusantara University, 2015)
Carnival clothing is one form of artists’ creativities in fine art, created in various functions. Those functions are viewed based on utility value and the purpose that consistently are embedded in an art work. In addition, several functions of carnival clothing were constructed on the basis of social and cultural conditions that are effective in a certain place. Each and every type of clothing raises perception to everyone else who sees it. Promotion of fashion style and industry through carnival clothing results in diverse perceptions acceptable to the viewers. Audience’s perceptions are also not apart from the key functions, social ones, and the physical ones of those carnival clothings themselves. Those three functions are the common ones of each art work created as communication tool with everyone else. The carnival clothings are communication tools of the fashion designer to the customers, communication between one customer and another one. On the carnival clothing there are also sources of knowledge science, history, technology, and many other explainable meanings. Through carnival clothings, the detectable issues in physical and non-physical structures are identifiable as well as they play role as the space to make more exploration on the dynamics of a community culture. This article aims to answer the functions of carnival clothing, using aesthetic approach, through the theory of clothing functions Roland Barthes and Edmund Burke Feldman’s art functions.